Integration of Artificial Intelligence in Foreign Language Teaching: Exploring Views and Beliefs of Greek Foreign Language Teachers - Varsamidou, Athina (International Journal of Language and Literary Studies, 2024)
The present quantitative research investigates attitudes and perceptions of Greek foreign language teachers regarding the issue of the use, implementation and pedagogical exploitation of AI in foreign language teaching. A total of 150 foreign language teachers in the public sector of primary and secondary education (permanent and contractual teachers) participated in the survey and the methodological tool used was an electronic questionnaire. The survey took place between March and May 2024. The research questions, which are the main axes of the survey, were the following: a) How do teachers define AI? b) Have they used AI tools in foreign language teaching and if so, why and how often? c) what do they consider to be the positive aspects of AI in teaching? d) what do they consider to be its negative aspects and what concerns do they have? e) to what extent do they feel competent in the use and pedagogical exploitation of AI applications? The results show that teachers perceive AI as something new that they are not well informed about and wish to be trained to be able to integrate it into their teaching. Among the positives, the speed of creating digital content is listed and among the negatives is the fear that there will be no need for foreign language teaching in the future and therefore no need for jobs for foreign language teachers. As far as their competence is concerned, the majority feel that support and training are needed in order to provide a valid framework for foreign language teaching.